Current practice of bedside teaching in undergraduate medical education of Bangladesh (Bangladesh Journal of Medical Education, 2017)
Introduction: Bedside teaching is the cornerstone of clinical teaching for the health professions. Different strategies have emerged to make it more effective. Many of the environments and opportunities available for bedside teaching and learning have changed.Methodology: This was a descriptive type of cross sectional study conducted in seven (three public and four private) medical colleges in Bangladesh over a period from July 2012 to June 2013 to determine the ways of conduction of bedside teaching in undergraduate medical education of Bangladesh. Total 30 Bedside teaching (BST) sessions conducted in the ward in Obstetrics and Gynaecology departments were observed by researcher herself and data was collected in a structured check list by using 5 points rubric (1-lowest quality, 5-highest quality). The checklist had four main sections- physical environment of bedside sessions, issues regarding patient's comfort and attitude towards patient, teaching tasks and group dynamics. Each section had a number of items and total 27 items were observed. For each variable frequency distribution, mean score and standard deviation (SD) were calculated.Here mean score 5- no need of further improvement, as it covered all the required criteria, 4- very minimum effort, 3- some effort, 2= moderate effort, 1= considerable efforts are needed to fulfill the required criteria.Result: Among physical environment factors the mean score of temperature, noise, space, teacher-student ratio were >2 but 3 but